Assessment of the effect of environmental pollution in a marina on caged mussels using chemical and genotoxic analysis. Issue 8 (13th September 2016) - Pazi, Idil; Kucuksezgin, Filiz; Kacar, Asli; Gonul, L. Tolga
ABSTRACT: An integrated approach using the contamination levels and DNA damage in mussels ( Mytilus galloprovinciali s) was applied in order to assess the chemical contamination in a marina (Eastern coastline of Aegean Sea). Mussels, which were harvested from a reference site (Foca), were transplanted into a marina situated along the coast of Izmir Bay. The transplanted mussels were collected at the 14th, 30th and 60th day of the experimental period. Polycyclic aromatic hydrocarbon (PAH) levels (27–51 ng g − 1 wet weight) detected in the mussels were similar to the levels detected in other coastal areas of the Mediterranean Sea. The marina's sediment was found to be contaminated with PAHs (∑PAH = 25 µg g −1 ) of pyrolytic origin and may become a source of pollution and a threat to the marine environment. In order to assess the DNA damage, the haemolymph and gill cells of the mussels were used for the comet analysis and considered as an indicator of exposure to genotoxic chemicals including 16 PAH compounds and metals. The highest levels of DNA damage expressed as %Tail-DNA (%T-DNA) were observed at the end of the experiment (21.5% T-DNA). The correlation analyses conducted between 2-, 3-, 4-ring PAHs in mussels and %T-DNA in haemolymph and gill cells showed a significant positive correlation. This investigation confirmed that transplanted mussel can be a useful tool to determine PAH contamination in marinas.